Dairy cattle lameness: a roundtable discussion. (1st May 2022) - Bell, Nick; Bacon, David; Craven, Emily; Crowe, Steve; Newsome, Reuben; Oikonomou, Georgios; Pedersen, Sara; Reader, Jon; Wilson, James
Foreword: Lameness in dairy cattle is a high prevalence condition with significant negative impact on the welfare and economics of the dairy herd. Most lameness is attributable to four main conditions: sole bruising (also referred to as sole haemorrhage), sole ulcer, white line disease and digital dermatitis. Understanding of the pathogenesis of major claw horn diseases has undergone a transformation in the last 20 years, with a shift from a primary nutritional aetiology to a biomechanical one. This has led to significant research into factors relating to claw biomechanics and interventions targeting the inflammatory process. Even for infectious conditions, the benefit of non-steroidal anti-inflammatory drugs to cow welfare and recovery cannot be underrated. In this roundtable discussion, the panel explore the clinical relevance of the findings of research exploring biomechanics and managing inflammation.